Evectivity Counseling Mothers Who Have Toddlers With Compliance In Giving Complementary Foods To Toddlers Stunting In Kelurahan Lembah Lubuk Manik Lingkungan 1 Year 2022 - Fauziah Gusvita Syarah Harahap (CV. AFDIFAL MAJU BERKAH, 2023)
Having a short body in a child who is below normal standards is the result of a condition of poor nutrition which in this condition has been going on for a long time. And most people think that this malnutrition may not understand the term stunting. Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for quite a long time, resulting in impaired growth in children, namely the child's height is lower or shorter (dwarf) than the standard age. The benefit of this research is to reduce the problems that occur in the village of Lembah Lubuk Manik Ling 1 by providing good solids and then to increase mother's knowledge about nutrition before pregnancy, during pregnancy, and after giving birth. The research design used an experimental Quasi-experimental design with a pretest and posttest sample design in this study as many as 51 mothers who had toddlers in neighborhood 1 of the valley of Lubuk Manik. counseling there is a significant change in the effectiveness of counseling for mothers who have toddlers with adherence to giving solids in cases of stunting. Whereas the average value of Observation I was Mean 3.97 and there was an increase in the average value of Observation 2, namely Mean 5.92 and there was an increase in the average value in Observation 3, namely Mean 6.00 so that it can be concluded that counseling was carried out effectively because there is an increase to improve nutritional needs. From the results of this study it is expected that neighborhood 1 mothers will be able to further improve and maintain efforts towards nutrition in children so that stunting does not occur. This health problem is a condition of a very short body in terms of the standard for measuring height according to age from WHO, therefore mothers who have been given counseling can ensure that it does not happen again to children at a later age.